Impact of pulmonary African trypanosomes on the immunology and function of the lung. - Mabille, D.; Dirkx, L.; Thys, S.; Vermeersch, M.; Montenye, D.; Govaerts, M.; Hendrickx, S.; Takac, P.; Van Weyenbergh, J.; Pintelon, I.; Delputte, P.; Maes, L.; et al. (Nat Commun, 2022)
Approximately 20% of sleeping sickness patients exhibit respiratory complications, however, with a largely unknown role of the parasite. Here we show that tsetse fly-transmitted Trypanosoma brucei parasites rapidly and permanently colonize the lungs and occupy the extravascular spaces surrounding the blood vessels of the alveoli and bronchi. They are present as nests of multiplying parasites exhibiting close interactions with collagen and active secretion of extracellular vesicles. The local immune response shows a substantial increase of monocytes, macrophages, dendritic cells and gammadelta and activated alphabeta T cells and a later influx of neutrophils. Interestingly, parasite presence results in a significant reduction of B cells, eosinophils and natural killer cells. T. brucei infected mice show no infection-associated pulmonary dysfunction, mirroring the limited pulmonary clinical complications during sleeping sickness. However, the substantial reduction of the various immune cells may render individuals more susceptible to opportunistic infections, as evident by a co-infection experiment with respiratory syncytial virus. Collectively, these observations provide insights into a largely overlooked target organ, and may trigger new diagnostic and supportive therapeutic approaches for sleeping sickness.
Keywords: Mice; Animals; *Trypanosomiasis, African/parasitology; *Tsetse Flies/parasitology; *Trypanosoma brucei brucei; Thorax; Pulmonary Alveoli